Understanding the E-Shopping Shift: Islamic Consumer Ethics and the Transition from Conventional to Online Shopping - Faisal Amri; Rasidah Novita Sari (LPPM Universitas Terbuka, 2025)
Technological advancements and the transition from traditional to online shopping have significantly impacted consumer behavior. The availability of various online marketplace platforms has changed shopping habits, modified purchasing trends, and shaped overall consumption decisions. This study examines the influence of income, Islamic financial literacy, and social media on consumer behavior in Java, Indonesia. This study used quantitative methods. Data were collected through questionnaires from residents of Central Java. The study sample, consisting of 530 respondents, was obtained using simple random sampling. The independent variables included income, Islamic financial literacy, and social media, while the dependent variable was consumer behavior. The data were analyzed using SmartPLS software, which involves a structural model (inner model) and a measurement model (outer model). This study revealed that Islamic financial literacy and social media have a significant impact on consumer behavior, while income showed no significant effect. The coefficient of determination (Adjusted R Square) of 0.702 (70%), indicates that income, Islamic financial literacy, and social media collectively influence 70% of consumer behavior, with the remaining 30% being due to unexplored factors. The transformation of the digital economy has had a multidimensional impact on consumption behavior, from psychological to economic. Therefore, understanding these changes is crucial for academics, business practitioners, and policymakers in designing adaptive strategies for the digital ecosystem.